The Role of Perceptions for Community-Based Marine Resource Management - Beyerl, Katharina; Putz, Oliver; Breckwoldt, Annette (Frontiers in Marine Science, 2016)
Every community-based marine resource management (CBMRM) inherently takes place in a highly complex social-ecological environment, and stakeholder perceptions related to various aspects of the natural and social environment guide behavior in every stage of the management process. This paper provides an introduction to the psychology of perception with regard to marine resource management. In particular, it offers a typology of CBMRM relevant perceptions along with an analysis of psychological, societal, and physical factors that modulate them. Based on this analysis, we propose the introduction of specially trained local Perception Experts (PE’s), whose role will be to recognize and reflect individual perceptions of involved stakeholders, and to communicate them at community meetings where decisions are made. This empirically testable addition to current CBMRM schemes could help to increase participation, develop management measures that fit the capacities of the involved stakeholders more accurately, and hence, contribute to a faster rehabilitation of marine resources.